Variations sur un thème : Les manières d’habiter des enfants dans les quartiers gentrifiés à Paris, Londres et San Francisco - Jean-Yves Authier; Sonia Lehman-Frisch (Métropoles, 2012)
The gentrification literature has developed a quite extensive knowledge of the neighborhood experience of adult residents. However the same is not true about children who are still understudied despite their visibility in many gentrified neighborhoods. This paper aims to fill this gap by examining the discourse, practice and sociability of children aged 9 to 11 in three gentrified neighborhood of Paris, London and San Francisco. It argues that the children fully invest the gentrified neighborhoods (which involve families) and that they are more exposed to “social diversity” than their parents and, more broadly, than the adults who live in these neighborhoods. Simultaneously the paper shows that the children’s ways of living and of co-existing in gentrified neighborhoods are marked by important differences. This results partly from their residential geographies and partly from their own social characteristics (social class, gender, age, position within the siblings…).